Prevalence and risk indicators of peri-implantitis in Korean patients with a history of periodontal disease: a cross-sectional study - Goh, Mi-Seon; Hong, Eun-Jin; Chang, Moontaek (Journal of periodontal & implant science, 2017)
The aim of this study was to analyze the prevalence and risk indicators of peri-implantitis in Korean patients with history of periodontal disease. A total of 444 patients with 1,485 implants were selected from patients who had been treated at the Department of Periodontology, Chonbuk National University Dental Hospital between July 2014 and June 2015. A group with a history of peri-implantitis (HP) (370 patients with 1,189 implants) and a group with a current peri-implantitis (CP) (318 patients with 1,004 implants) were created based on the radiographic and clinical assessments of implants. The prevalence of peri-implantitis was calculated at both the patient and implant levels. The influence of risk variables on the occurrence of peri-implantitis was analyzed using generalized estimating equations analysis. The prevalence of peri-implantitis in the HP and CP groups ranged from 6.7% to 19.7%. The cumulative peri-implantitis rate in the HP group estimated with the Kaplan-Meier method was higher than that in the CP group over the follow-up period. Among the patient-related risk variables, supportive periodontal therapy (SPT) was the only significant risk indicator for the occurrence of peri-implantitis in both groups. In the analysis of implant-related variables, implants supporting fixed dental prosthesis (FDP) and implants with subjective discomfort were associated with a higher prevalence of peri-implantitis than single implants and implants without subjective discomfort in the HP group. The presence of subjective discomfort was the only significant implant-related variable predictive of peri-implantitis in the CP group. Within the limitations of this study, the prevalence of peri-implantitis in Korean patients with a history of periodontal disease was similar to that reported in other population samples. Regular SPT was important for preventing peri-implantitis. Single implants were found to be less susceptible to peri-implantitis than those supporting FDP. Patients' subjective discomfort was found to be a strong risk indicator for peri-implantitis.